Woda, wino i tak dalej, czyli o napojach i trunkach w Konstantynopolu - Kokoszko, Maciej; Jagusiak, Krzysztof (Przegląd Nauk Historycznych, 2010)
The present article analyses the role of selected beverages in the diet of the inhabitants of the city of Constantinople between the IV and VII centuries AD. It concentrates mainly on water, phouska, wine and beer as they are pictured in medical (Dioscurides, Galen, Oribasius, Aetius of Amida, Anthimus and Paul of Aegina), culinary (De re coquinaria), agronomical (Geoponica) and other genres of literature (Athenaeus of Naucratis and patristic writings) of late antiquity and early Byzantium.